Interaction of sodium cholate with dioctadecyldimethylammonium chloride vesicles in aqueous dispersion - Alves, Fernanda Rosa; Feitosa, Eloi (Elsevier B.V., 2006)
Mixtures of dioctadecyldimethylammonium chloride (DODAC) cationic vesicle dispersions with aqueous micelle solutions of the anionic sodium cholate (NaC) were investigated by differential scanning calorimetry, DSC, turbidity and light scattering. Within the concentration range investigated (constant 1.0 mM DODAC and varying NaC concentration up to 4 mM), vesicle -> micelle -> aggregate transitions were observed. The turbidity of DODAC/NaC/water depends on time and NaC/DODAB molar concentration ratio R. At equilibrium, turbidity initially decreases smoothly with R to a low value (owing to the vesicle-micelle transition) when R = 0.5-0.8 and then increases steeply to a high value (owing to the micelle-aggregate transition) when R = 0.9-1.0. DSC thermograms exhibit a single and sharp endothermic peak at T-m approximate to 49 degrees C, characteristic of the melting temperature of neat DODAC vesicles in water. Upon addition of NaC, T-m initially decreases to vanish around R = 0.5, and the main transition peak broadens as R increases. For R > 1.0 two new (endo- and exothermic) peaks appear at lower temperatures indicating the formation of large aggregates since the dispersion is turbid. All samples are non-birefringent. Dynamic light scattering (DLS) data indicate that both DODAC and DODAC/NaC dispersions are highly polydisperse, and that the mean size of the aggregates tends to decrease as R increases. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: vesicle; micelle; vesicle-micelle transition; light scattering; differential scanning calorimetry; turbidity; DODAC; bile salts; sodium cholate